2011
DOI: 10.1902/jop.2010.100513
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐8 Gene Promoter Polymorphism (rs4073) May Contribute to Chronic Periodontitis

Abstract: Background The proinflammatory chemokine interleukin-8 (IL8) is important in the regulation of the inflammatory response. Single nucleotide polymorphism (SNP) rs4073 have shown that the A allele up regulates the IL8 levels after stimulation with lipopolysaccharides. We investigated the association of the SNP rs4073 with chronic periodontitis. Methods Genotyping was performed by standard polymerase chain reaction-restriction fragment length polymorphism assay in 289 genomic DNA samples of healthy control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 31 publications
6
63
0
Order By: Relevance
“…In another study of the association between the IL8 rs4073 and generalized chronic periodontitis, 36 the TA genotype was associated with increased risk, at a frequency of 52.8% in controls versus 74.6% in chronic periodontitis patients. In the current study, the authors found a frequency of 65.8% of the TA genotype in the generalized AgP patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study of the association between the IL8 rs4073 and generalized chronic periodontitis, 36 the TA genotype was associated with increased risk, at a frequency of 52.8% in controls versus 74.6% in chronic periodontitis patients. In the current study, the authors found a frequency of 65.8% of the TA genotype in the generalized AgP patients.…”
Section: Discussionmentioning
confidence: 96%
“…3436 A recent study with the same IL8 SNP (rs4073), also in a Brazilian population, 34 reported lack of association with chronic periodontitis. In a subsequent study, 35 these same authors investigated the SNP (rs4073) as part of combined haplotypes (−845TC, −738TA and −353AT), and reported that nonsmokers individuals carrying the TAT/CTA genotype were six times more likely to develop chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnic distribution of residents in São Paulo is 71.8% Caucasian, 4.2% African descendants, 22.6% Mulattos (children of intermarriages between Caucasians and African descendants), and 1.5% Japanese and Amerindian. 17 According to Callegari-Jacques and Salzano, [19][20][21] However, the Japanese population has rather limited genetic diversity, according to data from the Japanese Millennium Genome Project. 22 Population-specific SNPs may have important applications in anthropologic studies, such as studies of population genetic origins.…”
Section: Notesmentioning
confidence: 99%
“…. This SNP (-251T/A) was associated with chronic periodontitis and other diseases like bronchiolitis, oral squamous cell carcinoma, and gastric cancer 24,[30][31][32] . Our findings showed that the transcriptional activity of the IL8 gene mediating -845T was 9-fold higher than that mediating -845C in SCCTM cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, numerous SNPs have been found in the IL8 gene, some of which are known to be associated with susceptibility to diseases such as asthma and oral lichen planus 22,23) . A recent study showed that the SNP at position -251 of the IL8 promoter was associated with chronic periodontitis in Brazilian subjects 24) . Increased expression of the IL8 gene has also been observed in affected periodontal tissues 25) .…”
Section: Introductionmentioning
confidence: 99%